2012
DOI: 10.1038/am.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase in the water dispersibility of zinc phthalocyanine nanowires and applications in cancer phototherapy

Abstract: The phototherapy is one of the widely accepted noninvasive clinical methodologies to eradicate cancer cells owing to its minimal side effects and high selectivity to the light of specific wavelength. As represented by photodynamic (PD) and photothermal (PT) therapy, the phototherapy requires light and photosensitizer to generate reactive oxygen species and heat, respectively. Zinc phthalocyanine (ZnPc) is one of the promising photosensitizers as it has a strong absorption cross-section in the spectral range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
(33 reference statements)
1
44
0
Order By: Relevance
“…In this case, the desired solubility could be achieved by introducing several polar groups (for example, carboxylic or sulfonic) to the external benzene rings [18]. The other way of increased water dispersibility, with solubility increased from 16 to 120 mg/l, was recently reported as a result of ZnPc nanowire formation, directly grown from powdered ZnPc [17]. On the other hand, a basic (unsubstituted) ZnPc molecule could be selected as a good computational model, mimicking a less or more distorted structure of its more complex derivatives [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the desired solubility could be achieved by introducing several polar groups (for example, carboxylic or sulfonic) to the external benzene rings [18]. The other way of increased water dispersibility, with solubility increased from 16 to 120 mg/l, was recently reported as a result of ZnPc nanowire formation, directly grown from powdered ZnPc [17]. On the other hand, a basic (unsubstituted) ZnPc molecule could be selected as a good computational model, mimicking a less or more distorted structure of its more complex derivatives [18].…”
Section: Introductionmentioning
confidence: 99%
“…1a) is interesting primary due to the fact that Zn(II) ion with d 10 configuration does not contribute directly to the electronic spectra of phthalocyanine, dominated by transitions within their π-electronic system, formed by several conjugated C=N and C=C double bonds. Thus, reliable prediction of ZnPc molecular and electronic structure as well as spectroscopic properties could help in designing novel PDT agents [17], including their water-soluble derivatives, and understanding their action, based on photochemical reactions and electronic transitions between the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Pulses of light create more carboxylic acid end-groups and would allow a gradual increase in drug delivery as needed. Similar formation of acidic end-groups can be envisioned by other 'SMART' triggered events (for example, ultrasound, electrical signal, light, temperature 30 ) for switchable hydrophobic/hydrophilic surfaces. 31 This would allow modulation of drug release, and after the drug reservoir is exhausted, subsequent triggers would allow the forced erosion of medical implants, resulting in faster clearance.…”
Section: Discussionmentioning
confidence: 93%
“…Among the different photosensitizers in use today, metallo-phthalocyanine has attracted substantial interest due to their photodynamic (PD) properties that can be easily tuned by the type of metal ion involved. For example, zinc-phthalocyanine nanowires synthesized by Moon et al 71 showed excellent photosensitizing capabilities as well as highly efficient dual PD and photothermal (PT) effects upon irradiation of NIR laser. Studies performed by Jeong et al 70 also demonstrated the use of photosensitizer-conjugated human serum albumin NPs as impressive photodynamic drug delivery candidates with good biocompatibility and tumor-targeting abilities.…”
Section: Photo-triggered Therapy Using Nanocarriersmentioning
confidence: 99%